Analysis of structure importance of compensation capacitor in jointless track circuit. (March 2017) - Zhao, Linhai; Maggie Guo, Yi; Klein, Barbara D
This paper models the input signal amplitude of the main track and the small track of the adjacent jointless track circuit (JTC) when JTC is idle and the track circuit reader(TCR) received signal amplitude when JTC is occupied, based on the work mechanism of JTC and TCR. Based on the models, the relative impact of compensation capacitor on signal amplitude is obtained by simulation. The paper further proposes a calculation method for structure importance of compensation capacitors. Experimental results indicate that the rankings of structure importance are not affected by ballast resistance of JTC in this method. The results also show that the compensation capacitors closer to the receiving end are more important than those closer to the sending end. In addition, C2, C6, and C3 closer to receiving end are the most important and should be paid close attention during maintenance. The second, the first and the fifth capacitor from the sending end, have less impact on the JTC and TCR signal. This paper is helpful to determine the maintenance priority of each capacitor, optimize the maintenance strategy, and make better use of JTC.